Pengaruh karakteristik personal dan kinerja auditor terhadap tingkat penyimpangan prilaku dalam audit pada Kantor Akuntan Publik di Jakarta - Napitupulu, Bertha Elvy; Saragih, Rudy Hedianton (Journal of Information System, Applied, Management, Accounting and Research, 2021)
The purpose of this study was to analyze the effect of  personal auditor’s characteristics and the auditor‘s performance  on dysfunctional audit behavio u r ; . The population in this study were all auditors registered at the Public Accounting Firm in  Jakarta, totaling 83 auditors. The research sample was determined by purposive sampling method by considering the occupation and the area of ​​work. Researchers used questionnaires in soft copy form through social media such as Whatsapp, Linked in, and Facebook. The researcher uses multiple linear regression analysis model and other test and is processed using the Statistical Product and Services Solution  version 25 program. The results of this study indicate that the auditor's personal characteristics have a positive effect on dysfunctional audit behavior and auditor’s performance have a positive influence on the dysfunctional audit behavior .